Zavarovanje odgovornosti - Veberič, Jernej (Pravni letopis, 2020)
In Slovenia liability insurance is regulated in the chapter regarding insurance contract in articles 964 in 965 (only) of the Obligations Code. The regulation originates from the former Yugoslav Obligations Act from year 1978 which was modern at that time, but today it is considered deficient and outdated. Classic continental civil law approach is a good basis however it needs to be upgraded with up-to-date legislative solutions that are established in the Western European countries and are reflected in the Principles of European Insurance Contract Law - PEICL. This applies in particular to the concept of the insured event and to the issue of direct claims of third parties (victims). This article critically discusses some of the segments of the valid Obligations Code legal solutions and intertwines them with suggestions for a contemporary regulation which (based on the comparative legal practice) would be suitable for the Slovenian insurance and legal space.
Keywords: Slovenija; zavarovalno pravo; zavarovalstvo; zavarovanje odgovornosti